Facebook activity of residents and fellows and its impact on the doctor-patient relationship - Moubarak, Ghassan (Journal of medical ethics, 2011)
Aim Facebook is an increasingly popular online social networking site. The purpose of this study was to describe the Facebook activity of residents and fellows and their opinions regarding the impact of Facebook on the doctor-patient relationship.Methods An anonymous questionnaire was emailed to 405 residents and fellows at the Rouen University Hospital, France, in October 2009.Results Of the 202 participants who returned the questionnaire (50%), 147 (73%) had a Facebook profile. Among responders, 138 (99%) displayed their real name on their profile, 136 (97%) their birthdates, 128 (91%) a personal photograph, 83 (59%) their current university and 76 (55%) their current position. Default privacy settings were changed by 61% of users, more frequently if they were registered for >1 year (p=0.02). If a patient requested them as a ‘friend’, 152 (85%) participants would automatically decline the request, 26 (15%) would decide on an individual basis and none would automatically accept the request. Eighty-eight participants (48%) believed that the doctor-patient relationship would be altered if patients discovered that their doctor had a Facebook account, but 139 (76%) considered that it would change only if the patient had open access to their doctor's profile, independent of its content.Conclusions Residents and fellows frequently use Facebook and display personal information on their profiles. Insufficient privacy protection might have an impact the doctor-patient relationship.